Stock Market Co-Integration Evidence from Indonesia, Malaysia, South Korea, Hong Kong, and The US Stock Market - Alia Tri Utami (Universitas Islam Bandung, 2018)
ABSTRACT Financial liberalization conducted by many Asian countries has initiated significant growth in financial transactions and flow of funds in International financial markets hence increases the linkage between emerging stock markets with developed stock markets. The 2008 crash in the US stock markets has been the cause of the downslide in many stock markets in Asia along with outside Asia. However, this linkage indicates that international diversification cannot be implemented among these countries. This research aims to investigate the dynamic linkage of stock markets in Indonesia, Malaysia, South Korea, Hong Kong, and The US by applying the co-integration approach during the period of crisis and after the global economy crisis of 2008. Empirical result shows that Indonesia, Malaysia, South Korea, Hong Kong, and the US stock markets are co-integrated during and after the crisis. This empirical finding has important implications for the management of an international portfolio in the establishment of a stock portfolio in the Indonesian, Malaysian, South Korean, Hong Kong and the US stock markets. The result of this study shows that investors cannot get benefit if doing international diversification among the five stock exchanges. However, in the short term it is possible to obtain an excess return. ABSTRAK Liberalisasi keuangan yang dilakukan oleh banyak Negara Asia telah memprakarsai pertumbuhan yang signifikan dalam transaksi keuangan dan aliran dana di pasar keuangan internasional sehingga meningkatkan hubungan antara pasar saham berkembang dengan pasar saham maju. ‘Kecelakaan’ 2008 di pasar saham AS telah menjadi penyebab kemerosotan di banyak pasar saham di Asia bersama dengan di luar Asia. Namun, hubungan ini menunjukkan bahwa diversifikasi internasional tidak dapat diterapkan di antara negara-negara ini. Penelitian ini bertujuan untuk menyelidiki hubungan dinamis pasar saham di Indonesia, Malaysia, Korea Selatan, Hong Kong, dan Amerika Serikat dengan menerapkan pendekatan ko-integrasi selama periode krisis dan setelah krisis ekonomi global tahun 2008. Hasil empiris menunjukkan bahwa Indonesia, Malaysia, Korea Selatan, Hong Kong, dan pasar saham AS saling terintegrasi selama dan setelah krisis. Temuan empiris ini memiliki implikasi penting bagi pengelolaan portofolio internasional dalam pembentukan portofolio saham di pasar saham Indonesia, Malaysia, Korea Selatan, Hong Kong, dan AS. Hasil penelitian ini menunjukkan bahwa investor tidak dapat memperoleh manfaat jika melakukan diversifikasi internasional di antara lima bursa efek. Namun, dalam jangka pendek dimungkinkan untuk mendapatkan pengembalian yang berlebih.